IMPACT OF THE STATUS OF INSTITUTION AND FINANCIAL COMPENSATION ON THE DEPOSITION OF AN EMPLOYABLE WITH THE VALUE OF SERVICES 1 MAKASSAR - Muh. Restu Abadi Ruslan; Tenri Sayu Puspitaningsih Dipoatmodjo, Muh Ichwan Musa, Abdi Akbar, Rezky Amalia Hamka (ADISAM PUBLISHER, 2024)
This research aims to determine the influence of Leadership Style and Financial Compensation on Job Satisfaction of PDAM Service Region 1 Makassar employees. This research variable consists of leadership style and financial compensation as independent variables and job satisfaction as the dependent variable. This type of research is quantitative and associative. The population in this study was 127 employees of PDAM Service Area 1 Makassar. The sampling technique used in this research was the Slovin formula with a sample size of 56 respondents from the entire population. The data collection technique is carried out by distributing questionnaires to employees. The data analysis technique in this research uses simple regression with the help of SPSS version 25 software. The results of this research show that the leadership style variable has a positive and significant effect on job satisfaction. This is proven. Based on the results of the t test, the calculated t value is 5.783 > t-table 2.0048 and the significance is 0.000 < 0.05. The results of research on the financial compensation variable have no effect on job satisfaction for PDAM Service Region 1 Makassar employees. This is proven by the results of the t test which obtained a calculated t value of 0.660 > probability 0.05. Meanwhile, based on the research results, it can be concluded that leadership style and financial compensation have a positive and significant influence on the job satisfaction of PDAM Service Region 1 Makassar employees. Based on the results of the simultaneous test, the F-count value was 187.088 > 3.17 and the significance was 0.000 < 0.05 .